How is the provision of residential care to children under the age of 12 associated with changes in children's behaviour and mental wellbeing? - Catherine Nixon; Gillian Henderson (Scottish Journal of Residential Child Care)
Around 10% of children looked after in residential care in Scotland are aged 5-11. While there is a large body of evidence about the experiences of older children in residential care, little is known about the experiences of younger children in these settings. In this study we used routinely collected administrative data held by the Scottish Children’s Reporter Administration to: 1) identify common features in the familial, child protection and care histories of children under the age of 12 in residential care; 2) explore how being cared for in residential care prior to age 12 is associated with children's health and socioemotional wellbeing. Case file data from 135 children subject to compulsory measures of supervisions were examined. Our analysis indicated that younger children in residential care often have complex trauma histories, long histories of service involvement, and have often experienced repeat placement breakdowns that are attributed to the socioemotional and behavioural difficulties the children exhibit in placement. Being cared for in residential care provided a period of stability for younger children, with improvements seen in their socioemotional wellbeing and mental health in the 24 months following entry into residential care. Future research should focus on understanding the mechanisms underlying these changes.